21. LAPAROSCOPIC SURGICAL TREATMENT OUTCOMES OF ACUTE APPENDICITIS IN PREGNANT WOMEN AT HA DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: Thís research aiming to describe and comprehensively evaluate the laparoscopic surgical (LS) treatment outcomes of acute appendicitis (AA) in pregnant women at Ha Dong General Hospital.Research Method: A retrospective, descriptive study was conducted on 34 pregnant patients diagnosed with AA and treated with LS at Ha Dong General Hospital from January 1, 2021, to Dêcember 31, 2024. Data on patient characteristics, clinical and subclinical progression, detailed surgical techniques, complications, recovery time, and final treatment outcomes were collected and analyzed.Results: The average patient age was 30.6 ± 6.6 years, and the average gestational age was 15.1 ± 7.9 weeks. All patients (100%) underwent successful LS. The mean operative time was 42.5 ± 13.6 minutes; the group with AA complicated by peritonitis had a longer operative time (57.7 ± 7.5 minutes) compared to the uncomplicated AA group (37.2 ± 10.3 minutes) (p
Keywords: Acute appendicitis; Pregnancy; Laparoscopic surgery; Treatment outcomes; Ha Dong General Hospital